Occurrence of energetic extreme oceanic events in the Colombian Caribbean coasts and some approaches to assess their impact on ecosystems (2016)
Above-normal meteorological and oceanographic conditions that generate damage on coastal ecosystems and associated human communities are called extreme oceanic events. Accurate data are needed to predict their occurrence and to understand their effects. We analyzed available data from four localities in the Colombian Caribbean to study the effect of wave-related extreme events (hurricanes, surges) in three coastal ecosystems, i.e., mangroves, beaches, and reefs. Three localities were continental (Portete Bay mangroves at the Guajira Peninsula, Bocagrande Public Beach at Cartagena City, Tayrona Natural Park reefs near Santa Marta City), and one was oceanic (Old Providence Island reefs in the San Andres and Old Providence Archipelago, SW Caribbean). We gathered data on ocean surface winds (1978–2011) for the four locations, then modeled significant wave heights, then identified extreme events, and finally tried to identify effects on the ecosystems, directly or from published literature. Wave-related extreme surges were also compiled from Colombian press news (1970–2008). Modeled wave maximums (> 5 m significant wave height) and press-reported events coincided with hurricanes, extreme dry season, mid-summer drought and northern hemisphere winter cold fronts, with neither a relationship to ENSO events, nor a temporal trend of increase, excepting Portete Bay, with a marked increase after 1995. Changes in Portete Bay mangroves were analyzed from aerial photographs before and after Tropical Storm Cesar (1996). In the 38 years before Cesar there was mangrove inland colonization, with some loss associated to beach erosion, while during the 8 years following the storm there were localized retreats and important changes in vegetation composition related to the falling of large trees and subsequent recolonization by species that are faster colonizers, and changes in soil composition brought about by inundation. Cartagena's Bocagrande Beach was followed between 2009 and 2011 by video, and two events of strong retreat were observed in 2010, one associated to the arriving of cold fronts in March, and the other to the passing of Hurricane Tomas in November–December. Together, they produced > 90 m beach retreat. We identified modeled wave maximums during Hurricane Lenny (1999) at Santa Marta city, and hurricane Beta (2005) at Old Providence Island, both of which, according to the literature, had transient minor effects on local coral reefs, which had been more affected by diseases and bleaching.